Exploitation of Children Through Social Media in A Legal Perspective of Child Protection - Andri Anugerah Kusuma (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2021)
One of the important elements that must exist in a rule of law is the protection of human rights, where the inclusion of rights and human rights of citizens in the constitution brings consequences for the state to recognize, respect and respect and fulfill the rights of citizens, including in including the fulfillment of the basic rights of children. Children are a mandate and a gift from God Almighty, which is inherent within them of dignity as a whole human being. In line with the development of the times, which requires a transfer in all aspects of people's life, which can be done manually to completely digital or can be referred to as digitalization, which then with the Covid-19 pandemic that hit the world community became the biggest factor in the acceleration of digitalization where children Children in the compulsory education age category use social media as a learning medium which, if not closely supervised by parents, can raise concerns about child exploitation through social media, it is necessary to discuss in this study the forms of sexual violence that can occur against children. through social media, as well as forms of legal protection for child victims of sexual violence. The research method used in this research is juridical-normative legal research, with library material that includes primary legal materials, namely the 1945 Constitution, Law Number 39 of 1999 concerning Human Rights, and Law Number 35 of the Year. 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, then secondary legal materials which include previous legal research, legal books, scientific journals, and other legal materials, then finally tertiary legal materials covering Indonesian language , and an encyclopedia.